2017
DOI: 10.1016/j.apenergy.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

A new modified-serpentine flow field for application in high temperature polymer electrolyte fuel cell

Abstract: Flow field design for the distribution of reactants and products on the electrode surface plays an important role in the overall performance of the fuel cell. It acts as a crucial factor when the laboratory scale fuel cell is scaled up for commercial applications. In the present work, a novel flow field design is proposed and its usefulness for the fuel cell applications are evaluated in a high-temperature polymer electrolyte fuel cell. The proposed geometry retains some of the features of serpentine flow fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…(1)-(3) that H react is higher when W E , i.e., the power generation performance, is smaller, resulting that T react is higher according to Eq. (15). In addition, another reason might be that the condensation heat of accumulated water also contributed to the rise of the temperature.…”
Section: Impact Of Pem On Temperature Distributionmentioning
confidence: 99%
“…(1)-(3) that H react is higher when W E , i.e., the power generation performance, is smaller, resulting that T react is higher according to Eq. (15). In addition, another reason might be that the condensation heat of accumulated water also contributed to the rise of the temperature.…”
Section: Impact Of Pem On Temperature Distributionmentioning
confidence: 99%
“…Vazifeshenas et al [9] conducted a 3D simulation of a composite flow field, which retains the serpentine design and excels it in many aspects. Singdeo et al [10] proposed a multi-channel serpentine cross flow field, in which the reactant density varies between adjacent channels, and proved that the cross-diffusion improves the uniformity of gas distribution. In fact, multi-channel serpentine channel has been widely adopted thanks to its flexibility and applicability.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results indicated that the design is beneficial to water removal. Singdeo et al proposed a new modified multi‐serpentine flow field for high‐temperature polymer electrolyte fuel cells. Their modified flow field has enhanced the uniformity of current distribution over the active area compared to the conventional multi‐serpentine flow field.…”
Section: Introductionmentioning
confidence: 99%
“…As known that the modified multi‐serpentine flow field proposed by Singdeo et al is helpful to improving the distribution uniformity of reactant gas and current density, but they did not carry out detailed analysis. In this work, we presented two compensated flow fields, termed separated serpentine flow field and combined serpentine flow field following their designing principle.…”
Section: Introductionmentioning
confidence: 99%